Associations between Periapical Health of Maxillary Molars and Mucosal Thickening of Maxillary Sinuses in Cone-beam Computed Tomographic Images: A Retrospective Study - ERÇALIK YALÇINKAYA, ŞEBNEM (ELSEVIER SCIENCE INC, 2020)
Introduction: This retrospective study aimed to assess the radiologic characteristics of the possible associations between mucosal thickening of the maxillary sinuses (MSs) and periodontal and anatomic conditions of healthy and diseased maxillary teeth. Methods: The periapical health of the maxillary molars in cone-beam computed tomographic (CBCT) images from 50 patients (mean age = 40.60 +/- 14.59 years) was evaluated using the CBCT-periapical index. Anatomic associations between maxillary molars and the inferior wall of the MSs and periodontal bone loss and its relation to MS pathology were assessed. The possible effects of these conditions on mucosal thickening of MSs were analyzed. Kruskal-Wallis, Mann-Whitney U, chi-square, and logistic regression (for relative risk) tests were used for statistical analysis. Results: : CBCT-periapical index 4 was the most frequently encountered apical periodontitis (AP) lesion. The risk for pathologic changes in the MSs was significantly higher in the presence of AP (P < .001). This risk was 62.364 times greater than that in areas of MSs adjacent to healthy teeth of the same patient (95% confidence interval, 7.968-488.14). Thicker MS mucosae were detected when the molar roots with AP were closer to the MSs (P < .004). No statistically significant difference was found between periodontal status and MS pathology. Conclusions: The findings of this study showed that MSs were affected by the endodontic health of adjacent molar teeth. Dental and medical practitioners should take into consideration the possible odontogenic causes while examining pathologic changes in the MS.
Keywords: Apical periodontitis; mucosal thickening; odontogenic maxillary sinusitis; periodontal bone loss; periapical health; PERIODONTAL BONE LOSS; SCHNEIDERIAN MEMBRANE; APICAL PERIODONTITIS; ENDODONTIC TREATMENT; POSTERIOR TEETH; DIMENSIONS; LESIONS; FLOOR